Islam – the future civilisation of mankind: challenges and responses - Shehu, Fatmir Mehdi (International Institute of Islamic Thought East and South East Asia & International Islamic University Malaysia, 2017)
Ongoing bloodshed and conflict due to racial, social, cultural, political, and religious differences, along with developments in science, industry, infrastructure, arts and especially in information technology, are believed to be the real challenges facing contemporary societies, especially Muslims. What are the causes of these challenges? Do they have an intellectual, economic, political or social dimension? How can we respond to them? Who is responsible for the cause of these challenges – man or God? Islam with its sources of knowledge – Qur’Én and Sunnah, claims to provide for Muslims and humanity the proper measures to respond to contemporary challenges. Islam provides for humanity an enduring and authentic civilisation with a transcendental nature that promotes holistic justice, peaceful coexistence, mutual respect and better understanding. This chapter focuses on four main contemporary challenges witnessed especially by Muslims, i.e., the intellectual, economic, political and social and how to respond to them. The main objectives are to exhibit the role of the Islamic civilisation in responding to contemporary challenges and to show its unique paradigm shift in shaping the future civilisation of mankind. The descriptive and analytical methods will be. The author strongly believes that the chapter will contribute to the revival of Muslims’ understanding of the Islamic civilisation and its application to their day-to-day individual, familial, communal, and social lives. Besides, it will add to the existing knowledge and will be a reference for young students, intellectuals, scholars, leaders, governors, and researchers.